Studies on existing neonatal calf managemental practices adopted by dairy farmers of Tarai region of Uttarakhand - Tewari, Himani; Kumar, Sanjay; SINGH, D V; Prasad, Shiv; Rath, Rajashree (Indian Journal of Animal Production and Management, 2018)
field survey was conducted to collect the information on neonatal management practices followed bythe dairy animal owners in Tarai region of Uttarakhand. The results revealed that 100% of farmers cleanmucous membrane of newborn calf immediately after birth. Around 74.38% allowed suckling within 15minutes of birth and 23.12% between 30 minutes after birth. Majority of farmers 73.75% practiced feedingcolostrum within half an hour of its birth and continuing upto the first five days. Practice of cutting anddisinfection of navel cord after birth was uncommon (10%). Temporary identification method was commonas compared to permanent type which were 87.50% and 12.50% respectively. Most of farmers feed theircalves from two teats and 11.25% of farmers practice feeding of milk from all four teats. Dehorning wasdone by majority of the farmers (97.50%). Castration of male calves at 30-40, 40-50 and >50 days of agewere practiced by 42.50, 27.50 and 23.75% of farmers respectively. Weaning of calves was done at 40-60days of age by 83.12% of farmers.Key words: Colostrum, Dehorning, Neonates, WeaningIndian ranks first in the world in terms of milkproduction and contributes to about 14% of thetotal milk production of the world 3. Understandingthe factors affecting farmers’ adoption of dairytechnology is critical to success of developmentand implementation of policies and programmesin dairy industry development. Previous adoptionorientedresearch has examined the use anddiffusion of